Does Cd36 gene play a key role in disturbed glucose and fatty acid metabolism in Prague hypertensive hypertriglyceridemic rats? - Kadlecová, M; Cejka, J; Zicha, J; Kunes, J (Physiological research, 2004)
Close links between hypertension, hypertriglyceridemia, insulin resistance and other symptoms of metabolic syndrome was demonstrated in humans and experimental animals. Quantitative trait loci for defects in glucose and fatty acid metabolism, hypertriglyceridemia and hypertension were mapped in spontaneously hypertensive rats (SHR) on chromosome 4 and defective Cd36 gene was identified in this region. Here we investigated the polymorphism of Cd36 gene in Prague hereditary hypertriglyceridemic (HTG) rats, which represent another model of genetic hypertension and metabolic syndrome. These animals were compared with NIH-derived SHR and two different normotensive control strains (WKY, LEW). In spite of the fact that HTG and SHR rats had similar metabolic disturbances, genotype analysis of PCR products has shown that Cd36 mutation was not present in HTG rats. In conclusion, we have revealed that defective Cd36 is probably a candidate gene for disorded fatty-acid metabolism, glucose intolerance and insulin resistance in NIH-derived SHR, but other genes might play a role in pathogenesis of metabolic syndrome in Prague hereditary hypertriglyceridemic rats. This is in accordance with the absence of defective Cd36 gene in original SHR from Japan.
Keywords: hypertriglyceridemie; Humans; Phylogeny; polymorfismus genetický; Hypertension; Insulin Resistance; Rats, Inbred Lew; Rats, Inbred WKY; krysa rodu Rattus; lidé; zvířata; glukosa; Polymorphism, Genetic; potkani inbrední WKY; metabolický syndrom; Hypertriglyceridemia; mastné kyseliny; Male; inzulinová rezistence; hypertenze; fylogeneze; Metabolic Syndrome; Glucose; CD36 Antigens; potkani inbrední LEW; Rats; Animals; mužské pohlaví; Disease Models, Animal; antigeny CD36; Fatty Acids; modely nemocí na zvířatech